IDENTIFIKASI JAMUR PATOGEN PENYEBAB PENYAKIT TANAMAN KARET (Havea brasiliensis) Di SUKAJAYA KECAMATAN BAYUNG LINCIR KABUPATEN MUSI BANYUASIN SUMATERA SELATAN - Yuza Defitri (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
The research about identification of pathogenic fungi in rubber plant (Havea brasiliensis) In   Sukajaya Kecamatan Bayung Lincir Kabupaten Musi Banyuasin and Agriculture Quarantine Laboartory Jambi has been done for six months. The aim of research is to identificated disease in rubber  plants (Havea brasiliensis) that caused by fungi in Sukajaya Kecamatan Bayung Lincir Kabupaten Musi Banyuasin. The research  maked to see disease sign in rice plants area and to identificated pathogenic fungi in laboratory by microscop and fungi identifications book.The result of this research indicated that find four pathogenic fungi to attack rice plants in Lubuk Ruso Kabupaten Batanghari that is: 1)  Rigidoporus lignosus fungi caused White root fungus disease, 2) Fusarium sp fungi caused Rubber bark necrosis disease,            3) Colletotrichum  gloeosporiosides    fungi caused Colletotrichum  Leaf   disease and 4)  Phytopthora botryosa fungi caused  Phytopthora Leaf  disease. Key words : Identification, Patogenic fungi and Havea brasiliensis .